Big bang - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
Explores the Big Bang theory, that is prevailing cosmological model that describes the early development of the Universe.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi.
DVD format.
Keywords: Big bang theory; Cosmology